2011
DOI: 10.1016/j.pbb.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic–androgenic steroid effects on nociception and morphine antinociception in male rats

Abstract: The purpose of this study was to investigate the effects of acute and chronic administration of anabolic–androgenic steroids (AAS) on nociception and morphine antinociception in acute pain models, as well as on chronic inflammatory nociception. In Experiment 1, adult, gonadally intact male rats were injected s.c. for 28 days with either 5 mg/kg testosterone (T), dihydrotestosterone (DHT), stanozolol (STAN), or safflower oil vehicle (N = 12–25/group). On day 28, rats in each group were tested on acute thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…Consistently with this result, recent studies have shown that subcutaneous injections of testosterone, DHT, or stanozolol (5mg/kg; acute or chronic) did not alter pain nociception or induce chronic inflammatory pain in adult intact male rats (Tsutsui et al, 2011). However, we cannot rule out the possibility that 17 -meT elicited some kind of impulsivity effect, given that testosterone (5 mg/kg) displayed increased punished responses in the Vogel Conflict Test (Bing et al, 1998), although this measure is more associated with anxiolytic processes (Millan and Brocco, 2003) than to impulsivity.…”
Section: Discussionsupporting
confidence: 73%
“…Consistently with this result, recent studies have shown that subcutaneous injections of testosterone, DHT, or stanozolol (5mg/kg; acute or chronic) did not alter pain nociception or induce chronic inflammatory pain in adult intact male rats (Tsutsui et al, 2011). However, we cannot rule out the possibility that 17 -meT elicited some kind of impulsivity effect, given that testosterone (5 mg/kg) displayed increased punished responses in the Vogel Conflict Test (Bing et al, 1998), although this measure is more associated with anxiolytic processes (Millan and Brocco, 2003) than to impulsivity.…”
Section: Discussionsupporting
confidence: 73%
“…It is unlikely that this is due to proximate causes of increased hunger or insensitivity to pain. Chronic treatment with testosterone and other AAS at high doses in male rats does not increase food consumption (Bisschop et al, 1997; Lindblom et al, 2003) or reduce responsiveness to pain, including acute thermal and mechanical nociceptive stimuli applied to the paws as in the present study (Celerier et al 2003; Tsutsui et al, 2011). Instead, it might appear that testosterone reduces aspects of cognitive flexibility, to favor a “win-at-all- costs” approach to maximizing gains.…”
Section: Discussionmentioning
confidence: 43%
“…The intraplantar injection volume in rats was 200 μl. Positive controls were used at the following doses: 5 mg·kg −1 morphine in rats for analgesia (Tsutsui, Wood, & Craft, 2011), 3 mg·kg −1 morphine in mice for analgesia and constipation (Devilliers et al, 2013), 50 mg·kg −1 morphine in mice for respiratory depression (Devilliers et al, 2013), 15 mg·kg −1 morphine in mice for place preference conditioning (Francès, Smirnova, Leriche, & Sokoloff, 2004), 10 mg·kg −1 duloxetine for screening tests of antidepressant drugs (Zomkowski, Engel, Cunha, Gabilan, & Rodrigues, 2012) and 100 mg·kg −1 gabapentin in rats for neuropathic pain relief (Urban et al, 2005).…”
Section: Methodsmentioning
confidence: 99%